Giant Cell Arteritis: A Rare Cause of Thunderclap Headache in the Elderly - Garvita Agrawal; Manish Bhartiya; Vinny Wilson; Arindam Mukherjee; Vikram Singh (Journal of the Indian Academy of Geriatrics)
Giant cell arteritis (GCA) is a medium-to-large-vessel vasculitis affecting both intracranial and extracranial vessels. It generally presents with constitutional symptoms, headache, jaw claudication, and vision loss. Presentation as thunderclap headache is unusual. We present an unusual case of thunderclap headache in a middle-aged individual who was eventually diagnosed with GCA. The patient was diagnosed with a case of GCA based on clinical findings and temporal artery biopsy with a good response to treatment. GCA should be considered differential of thunderclap headache with normal imaging and cerebrospinal fluid findings.